Problem-Focused Coping as a Predictor of Psychological Well-Being in Individuals with Substance Use Disorder: Problem-Focused Coping and Psychological Well-Being - Jabbar, Tabasam; Khanum, Sanober; Imran, Hina (Pakistan Journal of Health Sciences, 2024)
The explanation of the term coping is how a person address challenging situations through different behavioral and cognitive strategies. Problem-focused coping include strategies through which a person focuses on finding the solutions to problem that leads to maintaining psychological well-being. Objective: To investigate the predictive association of problem-focused coping with individual’s psychological well-being in people grappling with substance use disorder. Method: The theoretical model of the study was based on Lazarus and Folkman’s Transactional Model of Stress and Coping and Six Factor Model of Psychological Well-Being The sample size comprised of 128 participants with substance used disorder between the ages 20 to 40 years old (M=30.14; SD=6.64). The entire sample was drawn from diverse Rehabilitation Centers located in Karachi. Participants were selected by using purposive sampling technique. In this study three measures were used; semi structure interview form, Ryff Scales of Psychological Well-Being-Urdu Version and the locally constructed Coping Styles Scale. Descriptive statistics and Linear Regression Analyses were utilized for sample characterization and to ascertain the predictive relationship between variables. Results: Results revealed that in those with substance use disorder, the use of problem-focused strategies significantly predicted the psychological well-being. Moreover, the analysis highlighted that problem-focused coping significantly predicted six dimensions of psychological well-being in this population. Conclusions: These findings underscore the importance of coping strategies in treating individuals with substance use disorder, facilitating effective stress management, and maintaining psychological well-being. Awareness campaigns supported by research helps in maintaining insight and positive mental health